PENGARUH PENGGUNAAN APLIKASI TIKTOK TERHADAP PERILAKU KECANDUAN SISWA SISWI SEKOLAH MENENGAH ATAS DI KOTA BATAM - Malau, Novita Octavia Mardalena; Rorong, Michael Jibrael (SCIENTIA JOURNAL, 2022)
Today's social media developments are changing the behavioral patterns of individuals. Oneof these social media is the Tiktok application. The application is currently favored by a widevariety of groups, from adults to teenagers to children. The purpose of this study is todetermine whether the use of the Tik-Tok application influences the addictive behavior ofhigh school students in Batam City. The research method used is a quantitative method.The study population was high school students from Batam City using a random samplingmethod. Data analysis techniques used descriptive statistical tests, classical hypothesistesting, simple linear regression, and hypothesis testing. From the simple linear regressionresults, the regression equation Y = 3.482 + 1.149 X has a positive effect between variableusage (X) and dependent behavior (Y) in the Tiktok application